Pomegranate (Punica granatum L.) flower improves learning and memory performances impaired by diabetes mellitus in rats - Cambay, Z.; Baydas, G.; Tuzcu, M.; Bal, R. (Akademiai Kiado Zrt, 2011)
Oxidative stress induced by diabetes mellitus leads to damages in the brain, as a consequence of which cognitive functions is impaired. Therefore, for the treatment of diabetes mellitus, in addition to antidiabetics, antioxidants are used to cope with oxidative stress. The antioxidant ability of pomegranate flowers (PGF) to cope with the oxidative stress was investigated. Rats were divided into five groups with 12 animals in each group as given below: control, diabetes (STZ), STZ + the PGF I (300 mg/kg/day), STZ + PGF II (400 mg/kg/day) and STZ + PGF III (500 mg/kg/day). The findings from Morris water maze and probe tests showed that the animals in STZ group had impairments in learning and memory performances compared to the control group. Supplementation of PGF led to improvements in learning and memory performances of diabetic rats. While lipid peroxidation (LPO) was increased (P< 0.001), glutathione (GSH) content was decreased (P< 0.001) in hippocampal tissue of STZ-induced diabetic rats when compared with control values. Supplementation of PGF restored the levels of LPO and GSH towards their control values. Daily PGF supplementation to diabetic rats reduced the increase in glial-fibrilar acidic protein (GFAP) contents induced by diabetes in the hippocampus, which was significant in STZ + PGF III in comparison to STZ group (p< 0.05). In conclusion, these observations suggest that PGF supplementation decreases oxidative stress and ameliorates impairment in learning and memory performances in diabetic rats. Therefore, we suggest that PGF supplementation may be clinically useful in treating neuronal deficit in diabetic patients. Keywords: cognitive functions, diabetes mellitus, pomegranate flowers,
Keywords: cognitive functions; diabetes mellitus; pomegranate flowers; GFAP; oxidative stress